2006
DOI: 10.3168/jds.s0022-0302(06)72467-5
|View full text |Cite
|
Sign up to set email alerts
|

Omitting the Dry-Off Period Negatively Affects Colostrum and Milk Yield in Dairy Goats

Abstract: Seventeen pregnant multiparous Murciano-Granadina dairy goats, kept in a semi-intensive exploitation system with once daily milking throughout lactation and 1 kidding per year (milk yield, 577 L/300 d), were used to study the effects of dry-off period length on performance during the subsequent lactation. Goats were mated at wk 29 of lactation and were assigned to 2 experimental groups according to dry-off treatment: goats that were dried off 56 d before expected kidding (D56; n = 9) and goats without dry-off … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
34
2
11

Year Published

2009
2009
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(53 citation statements)
references
References 29 publications
6
34
2
11
Order By: Relevance
“…Randomly assigning dry period in a controlled trial, using dairy goats where parity and the previous lactation's milk production is known (unlike in this study) is necessary to disentangle the effects of dry period length on metabolic function (similar to studies on cows; Rastani et al, 2005). However, as demonstrated by Caja et al (2006), assigning shorter dry periods may be difficult as lactation persistence varies in does, resulting in some spontaneous self-drying.…”
Section: Discussionmentioning
confidence: 90%
“…Randomly assigning dry period in a controlled trial, using dairy goats where parity and the previous lactation's milk production is known (unlike in this study) is necessary to disentangle the effects of dry period length on metabolic function (similar to studies on cows; Rastani et al, 2005). However, as demonstrated by Caja et al (2006), assigning shorter dry periods may be difficult as lactation persistence varies in does, resulting in some spontaneous self-drying.…”
Section: Discussionmentioning
confidence: 90%
“…However, similar results to those obtained in our study were found by Andrade et al (2008), who reported low yields of solids in the first week of lactation followed by increased values. Moreover, Caja et al (2006) reported lower levels of proteins, reaching only 72 % of the total protein in the colostrums of non-induced goats. According to the literature, these changes may be associated with the use of corticosteroids (Winger et al 1995).…”
Section: Discussionmentioning
confidence: 94%
“…O incremento do fluxo sanguíneo fornece os compostos necessários para a síntese do leite ocasionando um aumento no metabolismo das células epiteliais dos alvéolos (KOLB, 1984). A secreção produzida chamada colostro, é sintetizada devido aos efeitos inibitórios da progesterona e do estrógeno em um processo que ocorre na ausência da ordenha (CUNNIGAN, 2004 , 1974;QUILES et al, 1991;CHEN et al, 1998;LEVIEUX et al, 2002;ARGÜELLO et al, 2006;RUDOVSKY et al, 2008;YANG;ZHANG, 2009) Embora o alto teor de imunoglobulinas no colostro seja conhecido não há um consenso referente ao predomínio protéico que ocorre no início da lactação, pois alguns autores acreditam que ocorre um aumento de todas as proteínas nessa fase (QUILES et al, 1991;AULDIST et al, 1995;CUNNIGAN, 2004;MADSEN et al, 2004;TSIOULPAS;LEWIS, 2007), enquanto que outros autores associam a maior concentração de proteína no colostro aos menores valores de caseína com um predomínio das proteínas do soro lácteo (OYENIYI;HUNTER, 1978;CHEN et al, 1998;HENG, 1999;SGARBIERI, 2005;CAJA;SALAMA; MACH, 1970;MICUSAN;BORDUAS, 1976;HALLIDAY, 1978;HEARY JR.;DEVERY, 1980;RADOSTITS et al, 2000;YANG;ZHANG, 2009 mg/dL, respectivamente para cadeia leve) e valores inferiores no final do 1º mês de lactação (6,86±11,1 mg/dL, em primíparas e 12,9±10,2 mg/dL, em pluríparas para cadeia pesada e 11,8±22,2 mg/dL e 6,07±10,1 mg/dL, respectivamente para cadeia leve).…”
Section: Avaliação Da Influência Do Período Colostral E Do Primeiro Munclassified
“…Esses resultados estão de acordo com os autores que afirmam existir no início da lactação o predomínio das proteínas do soro lácteo (OYENIYI;HUNTER, 1978;CHEN et al, 1998;HENG, 1999;SANT´ANA, 2004;SGARBIERI, 2005;CAJA;SALAMA;.…”
Section: Avaliação Da Influência Do Período Colostral E Do Primeiro Munclassified
See 1 more Smart Citation